Poverty, undernutrition, and child mortality: some inter-regional puzzles and their implications for research and policy - Stephan Klasen (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2006)
This paper examines the relationship between measures of income poverty, undernourishment, childhood undernutrition, and child mortality in developing countries. While there is, as expected, a close aggregate correlation between these measures of deprivation, the measures generate some inter-regional paradoxes. Income poverty and child mortality is highest in Africa, but childhood undernutrition is by far the highest in South Asia, while the share of people with insufficient calories (undernourishment) is highest in the Caribbean. The paper finds that standard explanations cannot account for these inter-regional paradoxes, particularly the ones related to undernourishment and childhood undernutrition. The paper suggests that measurement issues related to the way undernourishment and childhood undernutrition is measured might play a significant role in affecting these inter-regional puzzles and points to implications for research and policy.
Keywords: I1; I3; O1; 330; Armut; Unterernährung; Kindersterblichkeit; Messung; Sozialer Indikator; Entwicklungsländer